2001
DOI: 10.1525/mp.2001.19.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the Discrimination of Musical Intervals: Going Out-of-Tune Is More Noticeable Than Going In-Tune

Abstract: Listeners were tested on their ability to discriminate "standard" and "comparison" pure-tone musical intervals that differed in size by 20 cents (1/ 5 of an equal-tempered semitone). Some of the intervals were prototypic, equal-tempered perfect fifths (exactly 7 semitones, or 700 cents). Others were mistuned to various degrees (660, 680, 720, or 740 cents). The intervals were melodic (sequential) in Experiments 1 and 2 and harmonic (simultaneous) in Experiment 3. Performance was neither enhanced nor impaired i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 82 publications
0
27
2
Order By: Relevance
“…Bartlett and Dowling showed that their order effects were not due to greater memorability of more tonal melodies, and Schellenberg (2002) explained that "going out-of-tune is more noticeable than going intune" when discriminating musical intervals. Both follow from Krumhansl's (1979 formalisation of contextual asymmetry -pitches not belonging to the current musical key are judged as more similar to pitches inside the key than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Bartlett and Dowling showed that their order effects were not due to greater memorability of more tonal melodies, and Schellenberg (2002) explained that "going out-of-tune is more noticeable than going intune" when discriminating musical intervals. Both follow from Krumhansl's (1979 formalisation of contextual asymmetry -pitches not belonging to the current musical key are judged as more similar to pitches inside the key than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when the initial pitch of a melodic interval is lower than the center of the musical pitch range, a descending interval will bring the second pitch further from the center than will a similarly sized ascending interval. Movement toward an unexpected event may be perceived as more salient than movement toward an expected event (see also Bartlett, 1993;Bharucha & Pryor, 1986;Schellenberg, 2001), and these differences in salience may be reflected in estimations of interval size.…”
Section: Logarithmic Mapping Of Fundamental Frequencymentioning
confidence: 99%
“…Alternatively, our findings may be related to other asymmetries in which it is easier to notice a change from a stable to an unstable representation than vice versa. In music perception, this asymmetry has been observed in moving from consonance to dissonance (Schellenberg, 2002), as well as from stable to unstable pitches within a key (e.g., G to F in the key of C; Krumhansl, 1990). As long as the initial key is, in some sense, psychologically stable, it may be easier to notice a departure from that key than an approach to a new one.…”
Section: Discussionmentioning
confidence: 99%